Professionalisation of African Healers: Apparent problems and constraints - Kottler, Amanda (PINS-Psychology in Society, 2025)
There is much talk afoot about the professionalization of African healers (or African medicine) but there is little evidence of any attempt to deconstruct the notions involved. I will examine the terminology and the assumptions embodied in a question which is commonly posed: What constraints are encountered in attempts at professionalization of African medicine? I then present three different positions from which to view African medicine, postulating that unless the different positions are acknowledged it remains impossible to address the question. Finding difficulty too with the notion of professionalization, I describe various ways in which the concept is viewed. Only after this ’deconstruction’ do I attempt to directly discuss some of the problematics raised by the question. By this stage it will have become obvious to the reader that there is no single answer. Instead, there are possible answers from each of the positions 1 outline. I point to a possible view that members of the ’western’ medical profession perceive African medicine as ’matter out of place’ and briefly outline this perspective. I suggest that, from this position, the solution to the ’problem’ is found in the idea of professionalization - i.e. in cleansing and purifying the polluted. My final thesis is that the process of professionalization is a rite of passage. This paper highlights that attempts at professionalization of African medicine involve not only a range of positions but also some hidden agendas.